Family information system / Che Chong Lee - Che, Chong Lee (2002)
Computer information system and computer applications are very important to an the organization. Thus the government is introducing the MSC or Multimedia Super Corridor. It is meant to develop Malaysia into a regional and international technology and telecommunications hub in 2020. The MSC will propel the transfer of technology and become the test bed for R&D in high-tech industries. Thus, Family Information System will be an example of what the function of family management in Smart Family will be like. The family management function i one most important feature in this system. This report is about the development of Family Information System, FemilyIS. The system provides the facility t keep track of the usage of assets in a family. It includes an asset module that will inventories special equipments and apparatus in a family. There are seven chapter in this proposal, which include Introduction, Literature Review, System Analyst, System Design, System Implementation, Testing and System Evaluation and Conclusion. The first four chapter are considered as phases that a system analysts need to go through before one can come out with clear and concise definitions of all the functional and non-functional requirements that are needed to develop a good application later in the future. The Inst three chapters are the remaining phases of system development, which use all findings and information gather in the earlier stages.